2015
DOI: 10.1097/pas.0000000000000392
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Analogue Secretory Carcinoma of Salivary Glands

Abstract: Mammary analogue secretory carcinoma (MASC) is a recently described low-grade carcinoma with morphologic and genetic similarity, including ETV6-NTRK3 fusion, to secretory carcinoma of the breast. ETV6 is frequently involved in other epithelial and nonepithelial tumors, and many fusion partners of ETV6 have been reported. In the present study, 14 Japanese MASC cases were clinicopathologically and molecularly analyzed. The median age of the patients was 39 years, and the male:female ratio was 6:8. All cases show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Skálová et al identified 5 SC cases with atypical junctions, exon 4 of ETV6 with exon 14 of NTRK3, and exon 5 of ETV6 with exon 14 of NTRK3 that have not been described in SC so far [16]. They also confirmed the observation of Ito et al that a subset of SC cases very likely harbors ETV6 fused with non-NTRK genes (ETV6-X fusion) [17]. Their study also suggested that cases with ETV6 gene fusing with genes other than NTRK3 or those cases displaying atypical exon junctions of ETV6-NTRK3 are associated with more aggressive/infiltrative histologic features of SC and less favorable clinical outcomes.…”
Section: Discussionmentioning
confidence: 60%
“…Skálová et al identified 5 SC cases with atypical junctions, exon 4 of ETV6 with exon 14 of NTRK3, and exon 5 of ETV6 with exon 14 of NTRK3 that have not been described in SC so far [16]. They also confirmed the observation of Ito et al that a subset of SC cases very likely harbors ETV6 fused with non-NTRK genes (ETV6-X fusion) [17]. Their study also suggested that cases with ETV6 gene fusing with genes other than NTRK3 or those cases displaying atypical exon junctions of ETV6-NTRK3 are associated with more aggressive/infiltrative histologic features of SC and less favorable clinical outcomes.…”
Section: Discussionmentioning
confidence: 60%
“…Before its designation as a separate entity, MASCs were predominantly grouped with other low-grade salivary cancer histologies [most commonly acinic cell carcinoma (AciCC)]. In 2010, identification of the ETV6-NTRK3 translocation t(12:15)(p13;q25) confirmed these tumors to be a molecularly distinct disease; the histologic resemblance to secretory carcinoma of the breast (which also harbors this fusion gene) inspired the designation ‘mammary analogue secretory carcinoma’ [ 2 , 3 ]. Of note, while ETV6-NTRK3 represents the most common fusion in MASCs, some cases have been found to harbor rearrangements involving ETV6 and a non- NTRK3 partner [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using paraffin tumor sections, we performed interphase FISH analysis for the gene splits in MYB , MYBL1 , and NFIB , as well as gene fusions between these genes when the gene splits were present. FISH procedures have been described elsewhere [ 7 , 59 ] and the FISH probes that we used are shown in Supplementary Table 2 . The frequencies of gene abnormalities were determined by counting >100 tumor cells.…”
Section: Methodsmentioning
confidence: 99%